Предоставление социальных услуг местными некоммерческими организациями: США и Россия - Мария Ватен; Скот Алард (Вопросы государственного и муниципального управления, 2014)
Provision of antipoverty and other social services by nonstate organizations is growing in importance in both the United States and the Russian Federation. The history of such provision in the United States may offer insights for the emerging system of nonstate provision in Russia. To illuminate these points, we provide historical overviews of both contexts and then we examine data from two surveys of social service organizations in the United States: the Multi-City Survey of Social Service Providers and the Rural Survey of Social Service Providers.We fid that nonstate actors strengthen social capital in poor neighborhoods and often link poor persons to public agencies. Nonstate actors strengthen other local institutions through programmatic partnerships and collaboration. However, financing arrangements of nonstate welfare provision may favor efficiency over concerns about equity, sustainability, and predictability. In addition, the primacy of nonstate provision leads to a welfare state that is more varied geographically than might be anticipated otherwise. Such variability appears to disadvantage highpoverty and predominately minority communities the most. Finally, politically, nonstate welfare provision may occur with little public discussion, debate, or reflection as it evolves over time. These findings invoke important questions for Russian policy-makers as they seek to develop an equitable and efficient means of providing assistance to their population.